Some innovations in pig farming and their zootechnical assessment - V. I. Khalak; B. V. Gutyj; O. M. Bordun (Ukrainian Journal of Veterinary and Agricultural Sciences)
The purpose of this work was to investigate the life expectancy, duration of breeding use, and reproductive qualities of sows of the large white breed of French selection, based on the obtained data to develop a new way of evaluating sows according to their operational value, as well as to calculate the economic efficiency of their use in the conditions of the industrial complex. The research was carried out in the conditions of the breeding plant for breeding large white pigs of Agroprime Holding LLC of the Odesa region and the animal husbandry laboratory of the Institute of Grain Crops of the National Academy of Sciences of the Russian Academy of Sciences. Evaluation of sows by indicators characterizing the level of their adaptation and reproductive qualities was carried out taking into account the following characteristics: life expectancy, months; duration of tribal use, months; received farts during the period of breeding use of all, received live piglets of all, head.; multifertility, goal; high fertility, kg; nest weight at the time of weaning at 28 days, kg; preservation of piglets until weaning, %. A comprehensive assessment of the sows of the general sample and different operational values was carried out according to the methodology of Berezovsky (2019) and biometric processing of research results – according to Kovalenko et al. (2010). It was established that the sows of the controlled population are characterized by high indicators of life expectancy, duration of breeding use, and reproductive qualities. Regarding fertility and litter weight at the time of weaning at 28 days, the sows of the controlled population belong to the elite class. A significant difference between sows of the category “high operational value” (I experimental group) and “low operational value” (II sub-experimental group) was established by the duration of life (7.9 months; td = 7.67), the duration of breeding use (8.3 months; td = 7.61), the number of farrowings obtained (1.7 farrowings; td = 9.44), the number of live piglets (24.9 goals; td = 10.50), multifertility (1.1 goals; td = 3.23), high fertility (0.03 kg; td = 0.67), the weight of the nest at the time of weaning at the age of 28 days (8.0 kilograms; td=3.07), survival of piglets before weaning (2.7 %; td = 1.52) and M. D. Berezovsky's index (3.43 points; td = 3.26). The number of reliable correlations between life expectancy, duration of breeding use, absolute indicators of reproductive qualities of sows, and the index “exploitation value of the sow” (EVS) is 75.0 %. The criterion for selecting sows of high operational value for the controlled population is the “EVS” index value at 220.90 or more points.